ESG Performance on Investment-Cash Flow Sensitivity: Case Study of Non-Financial Companies Listed on the Indonesian Stock Exchange - Novi Anri; Cynthia Afriani Utama (PT Mattawang Mediatama Solution, 2024)
This research aims to analyze the influence of ESG performance on Investment - Cash Flow Sensitivity of non-financial companies listed on the Indonesia Stock Exchange for the 2017-2022 period. ESG performance was measured using ESG ratings from Sustainalytics' ESG Research and Ratings, obtained from the Bloomberg Terminal database. Testing process was carried out on 50 registered non-financial companies in Indonesia for six years with a total of 300 observations obtained through purposive sampling techniques. The results of research employed panel balance data and the OLS method found that there are still phenomena Investment – Cash Flow Sensitivity occurred and good ESG performance could reduce Investment – Cash Flow Sensitivity. Thus, it can be indicated that companies implementing good ESG performance can more easily obtain funding sources.